Innovation in Designing a 500 kg Capacity Passenger Elevator in a Multi-Storey Building: A Study at Suzuya - Samuel Haris Purba (Journal of Golden Generation Engineering, 2025)
This study aims to analyze and design the working system of a passenger elevator, including the working mechanism of the elevator, the design of the lifting system, the calculation of cage capacity, the design of power and the selection of the main drive motor, the calculation of the main components, the design of the transmission, the calculation of maintenance costs, the selection of component materials, and the creation of technical drawings. The design results show that the specifications of the drive motor used have a power of 6.28 Hp with a rotation of 800 rpm, a lifting speed of 15 m/min, and a lifting capacity of 500 kg. The shaft components are designed using S45C carbon steel, with details of Shaft I with a diameter of 24 mm, Shaft II with a diameter of 41 mm, and Shaft III with a diameter of 41 mm. The gears consist of Gear I with a pitch circle diameter of 42 mm, a circle diameter of 37 mm, a head circle diameter of 46 mm, a width of 16 mm, and 21 teeth; Gear II with a pitch circle diameter of 210 mm, a circle diameter of 205 mm, a head circle diameter of 214 mm, a width of 16 mm, and 105 teeth; Gear III with a pitch circle diameter of 68 mm, a circle diameter of 63 mm, a head circle diameter of 108 mm, a width of 16 mm, and 34 teeth; and Gear IV with a pitch circle diameter of 270 mm, a circle diameter of 265.5 mm, a head circle diameter of 270 mm, a width of 16 mm, and 21 teeth. The drum used has a diameter of 253 mm, a weight of 100 kg, a length of 1073.79 mm, and a thickness of 16 mm.